2021
DOI: 10.1038/s41598-021-83196-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of karyopherin-β2 binding and nuclear import of ALS variants FUS(P525L) and FUS(R495X)

Abstract: Mutations in the RNA-binding protein FUS cause familial amyotropic lateral sclerosis (ALS). Several mutations that affect the proline-tyrosine nuclear localization signal (PY-NLS) of FUS cause severe juvenile ALS. FUS also undergoes liquid–liquid phase separation (LLPS) to accumulate in stress granules when cells are stressed. In unstressed cells, wild type FUS resides predominantly in the nucleus as it is imported by the importin Karyopherin-β2 (Kapβ2), which binds with high affinity to the C-terminal PY-NLS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 58 publications
5
55
0
Order By: Relevance
“…Our results now show that additional NTRs can perform similar functions. Of note, a subset of alternative NTRs has also been reported to interact with FUS during the review process of our article ( 52 ). Apart from TNPO1/2, TNPO3 (also known as transportin-SR2, Trn-SR2, Trn-3) and its splice variant transportin-SR ( 53 , 54 , 55 , 56 , 57 ) have been implicated in the nuclear import of several RBPs by binding to their arginine–serine (RS)-rich regions, both in a phosphorylation-dependent and phosphorylation-independent manner ( 29 , 57 ).…”
Section: Discussionmentioning
confidence: 91%
“…Our results now show that additional NTRs can perform similar functions. Of note, a subset of alternative NTRs has also been reported to interact with FUS during the review process of our article ( 52 ). Apart from TNPO1/2, TNPO3 (also known as transportin-SR2, Trn-SR2, Trn-3) and its splice variant transportin-SR ( 53 , 54 , 55 , 56 , 57 ) have been implicated in the nuclear import of several RBPs by binding to their arginine–serine (RS)-rich regions, both in a phosphorylation-dependent and phosphorylation-independent manner ( 29 , 57 ).…”
Section: Discussionmentioning
confidence: 91%
“…Unexpectedly, a significant fraction of the mouse FUS protein was found in the nucleus of adult Fus ∆NLS/∆NLS mice with hFUS transgene, albeit the endogenous FUS protein is completely truncated of the NLS. This is a priori surprising as the NLS is the major domain responsible for interaction with nuclear import receptors such as karyopherin ß2 [ 24 , 25 ]. There are at least two possible explanations to this observation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, nuclear import of FUS might be possible through NLS-independent mechanisms. Indeed, recent work has shown that ∆NLS mutants of FUS could still interact through RGG domains with karyopherin ß2 [ 24 , 25 ], as well as other nuclear import receptors [ 25 ] leading to significant nuclear import [ 24 ] .…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, protein cargo bear disease-linked mutations in the NLS, as with FUS P525L , in which the proline residue of the PY-NLS is mutated, or in FUS R495X , in which the PY-NLS is largely deleted ( Guo et al, 2019 ). These mutant forms of FUS are associated with very aggressive forms of early-onset ALS, and are more refractory to Kapβ2 activity ( Gonzalez et al, 2021 ; Guo et al, 2018 ). In sporadic ALS and other neurodegenerative diseases for which there is no clear genetic component, NIR levels may decline due to stress and aging or otherwise become less effective, as defects in nucleocytoplasmic transport are a key feature of many neurodegenerative diseases ( Guo et al, 2019 ; Kim and Taylor, 2017 ).…”
Section: Karyopherinsmentioning
confidence: 99%